Коваріаційний аналіз при обробці тривимірних зображень - Мигущенко, Руслан Павлович; Волобуєв, Максим Миколайович; Реброва, О. М. (НТУ "ХПІ", 2015)
Розглянуто питання автоматичного формування множин статистик Фішера, які однозначно характеризують стан об’єкта контролю, управління або ідентифікації, за рахунок використання методів статистичного аналізу. Формування множини F−статистик здійснюється застосуванням коваріаційного аналізу до тривимірних зображень об’єкта, шляхом проведення ряду перетинів вздовж осей аргументів. Результатом виконання перетинів є множини з координатами F₀, F₁, F₂, F₃. Проведені дослідження можуть бути використані для розробки алгоритмічного та програмного забезпечення засобів виявлення дефектів складного промислового обладнання. Розроблене програмне забезпечення може бути застосованим при імітаційному моделюванні.

The questions of automatic formation of Fisher statistics sets that uniquely characterize the state of the control or identification object by using methods of statistical analysis are considered. The effectiveness of the statistical approach to the analysis of the three dimensional model of the information signal conversion is proved. This analysis allows to reduce the dimension of images, thus highlighting four informative criterion F−statistics dispersion relations that have significant functional differences by type of object state control or management. The set of F-statistics is formed by the covariance analysis of the three-dimensional image of the object using a series of sections along the argument axes. The result of the process is a set with coordinates F₀, F₁, F₂, F₃. The obtained F-statistics being random variables with known distribution law, to assess the likelihood of error diagnosis on the basis of standard parametric models discriminant analysis. It is shown that the analysis of the covariance transformation plan allows to measure the localized spectraltime non-stationary signals. The research can be used to develop algorithmic and software defect detection complex industrial equipment. The developed software can be used for simulation.
Covariant analysis in the processing of three-dimensional images
Keywords: F−статистика; регресії; двовимірна модель; трансформація; архів даних; analysis of covariance; regression; two-dimensional model; transformation; data archive